Effects of Stereoscopic Display on Learning and User Experience in an Educational Virtual Environment. Issue 2 (1st February 2017) - Loup-Escande, Emilie; Jamet, Eric; Ragot, Martin; Erhel, Séverine; Michinov, Nicolas
ABSTRACT: Over the past decade, many studies have examined the potential benefits of educational virtual environments (EVEs), either by comparing them with other media or by assessing the effects of their features on learning. Paradoxically, very few of them have explored the effects of stereoscopic versus nonstereoscopic displays on learning and/or the subjective experience provided in an EVE. Our study was designed to fill this gap, by comparing the effects of these two virtual reality modes in an interactive mechanics learning task. We collected measures of task effectiveness (success/failure and completion time), learning outcomes and subjective experience (user experience, flow, and immersion). Results showed that (1) users were more successful in the learning tasks in the stereoscopic condition, and (2) perceived affective quality, flow, and immersion were better in this condition.